The Effectiveness of the Team Games Tournament Strategy in Improving Student Learning Outcomes in Islamic Religious Education Learning Class VIII SMP it Wildan Mamuju - Andi Fitri Nurhidayat; Muhammad Saleh; Firman; Muzakkir; Muh. Dahlan (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
his research aims to determine the application of the TGT strategy in Islamic Religious Education learning. To determine the increase in student learning outcomes in class VIII Islamic Religious Education learning at SMP IT Wildan Mamuju. And to find out the effectiveness of the TGT strategy in improving student learning outcomes in class VIII Islamic Religious Education learning at SMP IT Wildan Mamuju. This study uses a quantitative approach. The type of research used is quasi experimental design research. The population in this study was all 63 class VIII students. The sampling technique used was purposive sampling technique. The sample in this study was class VIII B which was divided into two groups, namely the experimental group of 16 people and the control group of 13 people. The research instruments used were observation and tests (pre test and post test) with data collection techniques being observation and documentation. The results of this research indicate that the application of the TGT strategy can improve student learning outcomes in class VIII PAI learning at SMP IT Wildan Mamuju. This is proven by the Paired Samples T Test (T test), which obtained a sig (2-tailed) value of 0.00 < 0.05, so it can be concluded that there is a significant difference between student learning outcomes in the pre-test and post-test data. Judging from the results of descriptive statistics in the Paired sample t test, the average (mean) value of the pre-test learning results was 52.5000, while the average (mean) value of the post-test learning results was 78.1875. This shows that the post test learning results are greater than the pre test learning results in the experimental group, so Ho is rejected and H1 is accepted. Therefore, it can be concluded that the application of the TGT type cooperative learning model can improve student learning outcomes in class VIII PAI Learning at SMP IT Wildan Mamuju.